Serum Biomarkers and Periodontal Disease in Gharyan Teaching Hospital Hemodialysis Libyan Patients - Wafaa Alhammali; M Jbireal, J (Khalij-Libya Journal of Dental and Medical Research, 2025)
Periodontal disease is increasingly recognized as a contributor to systemic inflammation and complications in patients with chronic kidney disease (CKD) undergoing hemodialysis. This study aimed to examine the association between serum biomarkers—including hemoglobin (Hb), creatinine, urea, uric acid, triglycerides, random blood sugar (RBS), and C-reactive protein (CRP) and periodontal disease in hemodialysis patients at Gharyan Teaching Hospital (GTH), with a focus on understanding their potential impact on systemic inflammation and disease management. A longitudinal observational study was conducted on male and female hemodialysis patients at Gharyan Teaching Hospital. Serum levels of the selected biomarkers were measured monthly over three months, alongside assessments of periodontal status. Spearman’s correlation analyses were used to explore relationships between serum biomarker levels and clinical variables, with significance set at p < 0.05. Among 99 patients (63 males, 36 females), xerostomia, gingival inflammation, and poor oral hygiene were observed in 58%, 65%, and 72%, respectively, with females more affected. Hemoglobin was low in 82%, while WBC and platelet counts were mostly normal; urea and creatinine were elevated in all. Bleeding on probing was strongly associated with worse periodontal outcomes: pathological probing depths (≥4 mm) and clinical attachment loss (≥3 mm) were more frequent in those with bleeding (98.5% vs. 59.4%, p < 0.001). Additionally, moderate to severe root exposure and abundant plaque were significantly higher in the bleeding group, whereas healthy pockets, normal gingival margins, and minimal plaque were more common among non-bleeding individuals (p = 0.001). The findings reveal gender-specific biochemical patterns in hemodialysis patients that may influence or reflect the systemic inflammatory burden related to periodontal disease. Elevated triglycerides linked with urea and associations between nutritional markers and uric acid highlight the metabolic disturbances exacerbated by renal dysfunction. The observed correlations between glucose metabolism and renal biomarkers in females emphasize the need to consider gender differences when addressing periodontal and systemic inflammation in this population. The significant associations, particularly between GI and CRP, support the inclusion of periodontal evaluation and care in the comprehensive management of hemodialysis patients. This study underscores the significant associations between serum biomarkers and systemic factors potentially related to periodontal disease in hemodialysis patients. The gender-specific variations in these associations highlight the importance of personalized monitoring and management of metabolic and inflammatory markers to improve outcomes for CKD patients undergoing hemodialysis, particularly in relation to periodontal health.